Emergency Department Utilization and Patient Outcomes During the COVID-19 Pandemic in America - Gutovitz, Scott (J Emerg Med, 2021)
BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic precipitated fear of contagion and influenced many people to avoid the emergency department (ED). It is unknown if this avoidance effected overall health or disease mortality. OBJECTIVE: We aimed to quantify the decreased ED volume in the United States, determine whether it occurred simultaneously across the country, find which types of patients decreased, and measure resultant changes in patient outcomes. METHODS: We retrospectively accessed a multihospital, multistate electronic health records database managed by HCA Healthcare to obtain a case series of all patients presenting to an ED during the early COVID-19 pandemic (March 1–May 31, 2020) and the same dates in 2019 for comparison. We determined ED volume using weekly totals and grouped them by state. We also recorded final diagnoses codes and mortality data to describe patient types and outcomes. RESULTS: The weekly ED volume from 160 facilities dropped 44% from 141,408 patients (week 1, March 1–7, 2020) to a nadir of 79,618 patients (week 7, April 12–18, 2020), before rising back to 105,667 (week 13, May 24–30, 2020). Compared with 2019, this overall decline was statistically significant (p < 0.001). The decline was universal across disease categories except for infectious disease and respiratory illnesses, which increased. All-cause mortality increased during the pandemic, especially for those with infectious disease, circulatory, and respiratory illnesses. CONCLUSIONS: The COVID-19 pandemic and an apparent fear of contagion caused a decrease in ED presentations across our hospital system. The decline in ED volume was associated with increased ED mortality, perhaps from delayed ED presentations.